Pengembangan Buku Cerita Bergambar pada Pembelajaran IPA untuk Meningkatkan Minat Baca Siswa Kelas IV SDN 04 Tente - Imam Kurniawan; Zulharman Zulharman; Zulkifli Zulkifli (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The purpose of this study was to develop a picture story book as a picture story book in science learning to improve the learning outcomes of grade IV students of SDN 04 Tente. The type of research used was R & D using the ADDIE development model including analysis, design, development, implementation, and evaluation activities. The results of the study showed that the results of the book development that was made could be used as a learning resource in thematic learning were declared valid. This can be seen from the results of expert validation consisting of media validation, language validation, and expert validation of learning. The picture story book as a learning resource in thematic learning obtained a value of 84.66% with a very feasible category. The picture story book as a learning resource in thematic learning was declared practical. The results of the questionnaire analysis filled out by 22 respondents/students with an average value of 97.36% in the very practical category. Meanwhile, the effectiveness of picture story books can be seen from the results of the t-test calculation that tℎ